The Efek Enzim Bromelin Buah Nanas (Ananas comosus (L.) Merr) Berbasis Sediaan Gel terhadap Lebar Intertubulus Dentin - Retno Dewi Alfiyanti; Berlian Prihatiningrum; Roedy Budirahardjo (UPT Percetakan dan Penerbitan Universitas Jember, 2019)
Caries tissue cleaning can use Chemo-Mechanical Caries Removal (CMCR) based on proteolytic enzymes that catalyze peptide bonds into simpler compounds. Proteolytic enzymes can be found in mature pineapple bromelain enzymes. The aim of the study is to determine the effect of gel-based bromelain enzyme with concentrations of 8%, 10% and 12% against the width of the intertubulus dentin. The bromelain enzyme is extracted using the Lowry method. Then purified using 80% ethanol and diluting become to concentrations of 8%, 10% and 12%. Diluted bromelain enzymes were formed in gel preparations based on HPMC and applied to the study sample. The results of this study indicated a widening of the intertubulus dentin. This is indicated by the variation of the dentin intertubulus width > 2µm. This widening occurs because the bromelain enzyme can hydrolyze collagen in intertubulus dentin in the absence of alpha-l-antitrypsin. Hydrolysis causes the breaking of hydrogen bonds in the triple helix- shaped tropocollagen to turn into strands of polypeptide chains. The bromelain enzyme with a concentration 10% is more effective than 8% and 12% because it is within the maximum speed limit of the enzyme so that the enzyme is saturated by its substrate and there is a difference in specific enzyme activity in each concentration.